New species of the spider genus Exocora Millidge, 1991 (Araneae: Linyphiidae) from Brazil - Lemos, Yuji; Brescovit, Antonio D. (Zootaxa, 2013)
The genus Exocora Millidge, 1991 is recorded from Brazil for the first time. Six new species herein are described and illustrated, all presenting male and female, from Atlantic Forest area. Exocora phoenix n. sp. is recorded in the states of Minas Gerais, Espírito Santo, São Paulo, Rio de Janeiro, Paraná and Santa Catarina, E. girotii n. sp. in the states of São Paulo, Rio de Janeiro, Paraná and Santa Catarina, E. ribeiroi n. sp. in São Paulo, Santa Catarina and Rio Grande do Sul, E. medonho n. sp. in Rio de Janeiro, E. nogueirai n. sp. in São Paulo and E. una n. sp. in Bahia.